Necessary qualities and values in the contemporary surgeon - Jorge Luis Estepa Pérez; Tahiluma Santana Pedraza; Jorge Luis Estepa Ramos (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Required qualities in surgeons have historically been an exceptional subject in the medical literature. Some highlight skills and resolving power, others their qualities as artists, craftsmen, technocrats and scientists. However, this is not enough to be a good surgeon. To that, it must be added responsibility, kind treatment, humanism, temperance of the character and the know how to work as a team, among many other characteristics. The purpose of this work is to reflect on the qualities and values of the contemporary surgeon.